2022
DOI: 10.1002/jso.26817
|View full text |Cite
|
Sign up to set email alerts
|

Aerobic fitness and muscle density play a vital role in postoperative complications in colorectal cancer surgery

Abstract: Background and Objectives To assess the association of preoperative aerobic fitness and body composition variables with a patient's resilience to the development and impact of postoperative complications after elective colorectal cancer (CRC) surgery. Methods Preoperative aerobic fitness was assessed by steep ramp test performance. Preoperative body composition was assessed by muscle mass and density determined from preoperative computed tomography scan analysis at the L3‐level. Complication development and se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 44 publications
0
5
0
Order By: Relevance
“…Benedek et al [11] discovered that TPA was related to postoperative complications instead of PMD, consistent with Wu et al [9]. However, Pekařová et al [12] and Cuijpers et al [13] unveiled that PMD was correlated with postoperative complications rather than TPA. Although the indicators of sarcopenia are controversial, the number of cases in our study can tackle this di culty.…”
Section: Introductionmentioning
confidence: 65%
“…Benedek et al [11] discovered that TPA was related to postoperative complications instead of PMD, consistent with Wu et al [9]. However, Pekařová et al [12] and Cuijpers et al [13] unveiled that PMD was correlated with postoperative complications rather than TPA. Although the indicators of sarcopenia are controversial, the number of cases in our study can tackle this di culty.…”
Section: Introductionmentioning
confidence: 65%
“…In recent years, there have been reports not only on the volume and the area of skeletal muscle but also on the skeletal muscle density, with individuals having low skeletal muscle density often referred to as having myosteatosis [36][37][38][39][40]. Moreover, muscle density can also be measured using CT, similar to PA and PV.…”
Section: Discussionmentioning
confidence: 99%
“…The SRT WR peak is equal to 148% of the CPET WR peak , while the peripheral muscle strength is the predominant limitation of SRT performance. Previous studies reported that preoperative SRT (1 W/s) performance (WR peak , W/kg) is inversely associated with the risk of adverse postoperative outcomes after hepatic, 18 pancreatic, 19 and colorectal resection 20,21 . However, a test‐specific cutoff and multivariate predictive model including the SRT performance that can be used to classify patients at low versus high risk for adverse surgical outcomes are lacking; therefore, further research is required.…”
Section: Solutionmentioning
confidence: 99%